2016
DOI: 10.1080/0972060x.2014.890076
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Antimicrobial Activity of Essential Oils ofOcimum basilicum,Ocimum canumandOcimum gratissimumin Function of Harvesting Time

Abstract: Abstract:The chemical composition of essential oils obtained by hydrodistillation from aerial parts of Ocimum basilicum, Ocimum canum and Ocimum gratissimum from Benin as affected by harvesting time, were analyzed by GC-FID (Gas chromatography-Flame ionization detector) and GC-MS (Gas chromatographyMass spectrometry). Based on the composition analysis, major components were as follows: estragol (43.0 -44.7 %) and linalool (24.6 -29.8 %) in O. basilicum oils; carvacrol (12.0 -30.8 %) and p-cymene (19.5 -26.2 %)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 40 publications
(79 reference statements)
3
23
0
Order By: Relevance
“…Among Gram-negative bacteria, Salmonella enterica, Shigella flexneri, Klebsiella pneumoniae, and Xanthomonas axonopolis were responsive to the EO antimicrobial effect, with inhibition occurring at 2.5-10.0 mg/mL MIC. Mith et al (2016) found a low antimicrobial activity of the basil EO for Salmonella enterica and L. monocytogenes. These authors also found linalool (24.6-29.8%) and estragole (43-47.7%) as major compounds of the basil EO.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among Gram-negative bacteria, Salmonella enterica, Shigella flexneri, Klebsiella pneumoniae, and Xanthomonas axonopolis were responsive to the EO antimicrobial effect, with inhibition occurring at 2.5-10.0 mg/mL MIC. Mith et al (2016) found a low antimicrobial activity of the basil EO for Salmonella enterica and L. monocytogenes. These authors also found linalool (24.6-29.8%) and estragole (43-47.7%) as major compounds of the basil EO.…”
Section: Resultsmentioning
confidence: 99%
“…Some researchers have reported that antimicrobial activities of the basil EO are predominantly associated with its major constituents: estragole and linalool (Elansary et al, 2016;Mith et al, 2016;Avetisyan et al, 2017;Hanif et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The studies related to the efficacy of essential oil of Ocimum gratissimum against gram-negative [25][26][27][28], gram-positive bacteria [25][26]35], fungi [30,36], and its regular consumption as spice without affecting the activities of conventional antibiotics [37], makes it a strong antimicrobial herbal product throughout the tropics.…”
Section: Ocimum Gratissimum-exploring Potentiality As An Essential Oimentioning
confidence: 99%
“…Plant oil is considered the Mother Nature's chemical factory [20] shows a unique composition of alcohols, aldehydes, ketones, ethers, esters, lactones, oxides, peroxides [21], tannins [22] and flavonoids [23]. The plant obtained from various regions in Africa mainly contain eugenol, thymol, methyl eugenol, camphor, (Cis)-ocimene, (trans)-ocimene, β-pinene, gramicidin D, (trans)-caryophyllene, Γ-terpinene and p-cymene [24][25][26]. Brazilian and Asian races contain phenylephrine (eugenol) as the chief constituent [27][28][29] along with sesquiterpene (caryophyllene), monoterpenes (β-ocimene) [25], bornyl acetate and some non terpene components [30].…”
Section: Ocimum Gratissimum-exploring Potentiality As An Essential Oimentioning
confidence: 99%
See 1 more Smart Citation